1924
DOI: 10.1002/cber.19240570219
|View full text |Cite
|
Sign up to set email alerts
|

Über die Kontakt‐Kondensation des Acetylens

Abstract: Bekanntlich hat bereits 1858 B e r t h e l o t l ) festgestellt, daB C h l o r of o r m sich h i Rotglut unbr dem EinfluD von mtallischem Kupfer untep Bildung von A c e t y 1 e n zerwtzt, w&hrlend B r o m o f o r m unter den gleichen Bdngungen, besondars abler beim Ersatz des Kupfms durch Eisen, neben Acetylen auch B e n z o 1 liefert. Diese iiberaus wichtige Reaktion, die B e rt h e 1 o t auf teine Kondensation des Acetylens in statu nascedi zuruckf ijhrte,.beleuchtete init leinem Schlage und in vollig unerwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1926
1926
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Carboxyl groups were converted to methyl groups to facilitate separation and identification. Different methods for this conversion involving rather harsh conditions have been described in the past (36)(37)(38)(39)(40)(41)(42)(43). To minimize structural rearrangements while obtaining nearly quantitative conversions, the three-step transformation (44, 45) outlined in Figure 2 was developed for a mixture of crude oil carboxylic acids.…”
Section: Sulfur Compounds Benzdinaphthenesmentioning
confidence: 99%
“…Carboxyl groups were converted to methyl groups to facilitate separation and identification. Different methods for this conversion involving rather harsh conditions have been described in the past (36)(37)(38)(39)(40)(41)(42)(43). To minimize structural rearrangements while obtaining nearly quantitative conversions, the three-step transformation (44, 45) outlined in Figure 2 was developed for a mixture of crude oil carboxylic acids.…”
Section: Sulfur Compounds Benzdinaphthenesmentioning
confidence: 99%
“…Previous work has shown that it is possible to produce benzene from acetylene on a variety of metal surfaces under both ultra-high vacuum (UHV) and reaction conditions. 9–35 For example, Tysoe et al showed acetylene forms benzene and ethylene on a Pd(111) surface and that increasing the surface acetylene coverage increased the yield of benzene. 36 In addition, the authors observed a threshold acetylene coverage of 0.3 ML, below which benzene formation does not occur.…”
Section: Introductionmentioning
confidence: 99%
“…Although carbon materials are usually considered as nonreactive supports for metal particles, increasing evidence suggests the inherent catalytic activity of carbon materials themselvesa phenomenon known as carbocatalysis. As early as in 1866, Berthelot reported carbocatalytic pyrolysis of acetylene, which he applied to synthesize benzene in the presence of carbon . Later, in the 1920s, the synthesis of benzene by acetylene condensation on charcoal was carried out by Zelinsky. From 1925–1930, activated charcoal was shown to mediate aerobic oxidation reactions. In spite of the long history of carbocatalytic transformations, their mechanisms remained largely incomprehensible due to the extraordinary complexity of the catalytic processes involving fluxional (metastable) active centers at the carbon surface. , …”
Section: Introductionmentioning
confidence: 99%